2013
DOI: 10.1308/003588413x13629960048190
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional assessment of hand outcome

Abstract: Introduction Patient reported outcome measures are central to National Health Service quality of care assessments. This study investigated the benefit of elective hand surgery by the simultaneous analysis of pain, function and appearance, using a three-dimensional (3D) graphical model for evaluating and presenting outcome. Methods A total of 188 patients scheduled for surgery completed pre- and postoperative questionnaires grading the severity of their pain, dysfunction and deformity of their hand(s). Scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“… 10 14 Assessing aesthetics can be a powerful method of demonstrating the patients’ perspective on surgical interventions. 15 17 For example, Chung et al 16 found that hand appearance is a valued outcome for rheumatoid arthritis patients with severe hand deformity undergoing silicone metacarpophalangeal arthroplasty. In fact, aesthetic consideration was the most important outcomes domain over function.…”
mentioning
confidence: 99%
“… 10 14 Assessing aesthetics can be a powerful method of demonstrating the patients’ perspective on surgical interventions. 15 17 For example, Chung et al 16 found that hand appearance is a valued outcome for rheumatoid arthritis patients with severe hand deformity undergoing silicone metacarpophalangeal arthroplasty. In fact, aesthetic consideration was the most important outcomes domain over function.…”
mentioning
confidence: 99%